2022
DOI: 10.3847/1538-4357/ac85b4
|View full text |Cite
|
Sign up to set email alerts
|

The Core Population and Kinematics of a Massive Clump at Early Stages: An Atacama Large Millimeter/submillimeter Array View

Abstract: High-mass star formation theories make distinct predictions on the properties of the prestellar seeds of high-mass stars. Observations of the early stages of high-mass star formation can provide crucial constraints, but they are challenging and scarce. We investigate the properties of the prestellar core population embedded in the high-mass clump AGAL014.492-00.139, and we study the kinematics at the clump and clump-to-core scales. We have analyzed an extensive data set acquired with the Atacama Large Millimet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 81 publications
(154 reference statements)
1
13
0
Order By: Relevance
“…The C 18 O emission, along the line of sight, presents asymmetric profiles toward some of cores. These line features in our sample can be attributed mostly to multiple velocity components because the C 18 O is virtually always optically thin in this sample (see Sabatini et al 2022), and these multiple velocity components match those of N 2 H + (J = 1-0) and ortho-H 2 D + (1 1,0 −1 1,1 ) toward G14.49 (the latter two lines are from Redaelli et al 2022). In order to fit the C 18 O emission associated to the cores, the central velocity derived from the other dense gas tracers (i.e., DCO + , N 2 D + , CH 3 OH, or H 2 CO) was used to guide the Gaussian fit of the C 18 O line.…”
Section: Properties Of the Molecular Line Datamentioning
confidence: 66%
See 1 more Smart Citation
“…The C 18 O emission, along the line of sight, presents asymmetric profiles toward some of cores. These line features in our sample can be attributed mostly to multiple velocity components because the C 18 O is virtually always optically thin in this sample (see Sabatini et al 2022), and these multiple velocity components match those of N 2 H + (J = 1-0) and ortho-H 2 D + (1 1,0 −1 1,1 ) toward G14.49 (the latter two lines are from Redaelli et al 2022). In order to fit the C 18 O emission associated to the cores, the central velocity derived from the other dense gas tracers (i.e., DCO + , N 2 D + , CH 3 OH, or H 2 CO) was used to guide the Gaussian fit of the C 18 O line.…”
Section: Properties Of the Molecular Line Datamentioning
confidence: 66%
“…In addition, the filamentary structures connected to cores can also transport material from the parental clump onto cores and thus further increase their masses. For example, the mass flow rate along a filamentary structure feeding a protostellar core in one of the ASHES targets, G14.49, is about 2.2 × 10 −4 M e yr −1 (Redaelli et al 2022). Such accretion rates along filamentary structures are not unusual in high-mass star-forming regions (e.g., Sanhueza et al 2021).…”
Section: Are Massive Cores More Unstable?mentioning
confidence: 99%
“…In spite of infall rate estimations being so far rare in IRDCs, the few examples available (Contreras et al 2018;Chen et al 2019;Redaelli et al 2022) suggest that cores with masses as those found in ASHES cores can grow significantly in mass in a core freefall time (as discussed in two ASHES clumps; Contreras et al 2018;Redaelli et al 2022). Some ASHES cores have the conditions to become massive as hot cores and form high-mass stars.…”
Section: Early Phase Of High-mass Star Formationmentioning
confidence: 99%
“…Higher-angular resolution NH 3 observations could potentially probe whether there is a connection and/or ongoing accretion from cloud and/or filament down to core scales (e.g. Redaelli et al 2022), since NH 3 can be used to identify the presence of dense gas.…”
Section: The Reliability Of the Standard Classification Scheme For Ou...mentioning
confidence: 99%